Role of Rubrics and Gifted Students. Issue 4 (October 2019) - Kaplan, Sandra N.
This column examines the role of rubrics in evaluating gifted students' performance as a part of examining issues surrounding the overall evaluation of gifted programs. The author examines how rubrics can be responsive to the group of gifted students and still be cognizant of the individual gifted learner who has specific talents, potential, and abilities. Three issues relating to the use of rubrics are discussed: verbiage, point allocations, and student voice.